Effect of deferiprone or deferoxamine on right ventricular function in thalassemia major patients with myocardial iron overload - Smith, Gillian C (BioMed Central, 2011)
BACKGROUND: Thalassaemia major (TM) patients need regular blood transfusions that lead to accumulation of iron and death from heart failure. Deferiprone has been reported to be superior to deferoxamine for the removal of cardiac iron and improvement in left ventricular (LV) function but little is known of their relative effects on the right ventricle (RV), which is being increasingly recognised as an important prognostic factor in cardiomyopathy. Therefore data from a prospective randomised controlled trial (RCT) comparing these chelators was retrospectively analysed to assess the RV responses to these drugs. METHODS: In the RCT, 61 TM patients were randomised to receive either deferiprone or deferoxamine monotherapy, and CMR scans for T2* and cardiac function were obtained. Data were re-analysed for RV volumes and function at baseline, and after 6 and 12 months of treatment. RESULTS: From baseline to 12 months, deferiprone reduced RV end systolic volume (ESV) from 37.7 to 34.2 mL (p = 0.008), whilst RV ejection fraction (EF) increased from 69.6 to 72.2% (p = 0.001). This was associated with a 27% increase in T2* (p < 0.001) and 3.1% increase in LVEF (p < 0.001). By contrast, deferoxamine showed no change in RVESV (38.1 to 39.1 mL, p = 0.38), or RVEF (70.0 to 69.9%, p = 0.93) whereas the T2* increased by 13% (p < 0.001), but with no change in LVEF (0.32%; p = 0.66). Analysis of between drugs treatment effects, showed significant improvements favouring deferiprone with a mean effect on RVESV of -1.82 mL (p = 0.014) and 1.16% for RVEF (p = 0.009). Using regression analysis the improvement in RVEF at 12 months was shown to be greater in patients with lower baseline EF values (p < 0.001), with a significant difference in RVEF of 3.5% favouring deferiprone over deferoxamine (p = 0.012). CONCLUSION: In this retrospective analysis of a prospective RCT, deferiprone monotherapy was superior to deferoxamine for improvement in RVEF and end-systolic volume. This improvement in the RV volumes and function may contribute to the improved cardiac outcomes seen with deferiprone.